2021
DOI: 10.3390/ijerph18168346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Time and Pre-Etching Treatment of CR-39 Detectors on Their Response to Alpha Radiation Exposure

Abstract: Radon passive monitors based on solid state nuclear track detectors (SSNTD), especially CR-39, are widely used in radon and thoron studies. They may be subjected to the influence of external factors, like changing of temperature, humidity, and pressure, both before and during the measurement. Evaluation of the exposed detectors involves chemical processing, whose conditions also influence the measurement results. The aim of this study was to check several factors, as to whether they may modify the response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Evaluation of the exposed detectors involves chemical treatment, the conditions of which also affect the measurement results. These phenomena were studied by Janik et al [ 7 ]. These authors concluded that (1) track density dependence of the age of production was statistically insignificant; and (2) simple pretreatment methods using hot water and carbon dioxide could be applied to improve the performance of nuclear track detectors.…”
mentioning
confidence: 99%
“…Evaluation of the exposed detectors involves chemical treatment, the conditions of which also affect the measurement results. These phenomena were studied by Janik et al [ 7 ]. These authors concluded that (1) track density dependence of the age of production was statistically insignificant; and (2) simple pretreatment methods using hot water and carbon dioxide could be applied to improve the performance of nuclear track detectors.…”
mentioning
confidence: 99%